Anthropogenic noise exposure suppresses the immune response in Mytilus spp. following Vibrio splendidus challenge - Chapuis, Ambre F.; Wale, Matthew A.; Bailey, Morgan; Farley, Hannah M.; Bean, Tim P.; Regan, Tim (Frontiers in Immunology, 2025)
IntroductionAnthropogenic noise is a growing environmental stressor in marine ecosystems, yet its effects on immune function in bivalves remain poorly understood.MethodsThis study examined the transcriptional response of blue mussels, Mytilus spp., following exposure to ship noise for seven days, followed by a low-dose Vibrio splendidus bath challenge.ResultsTranscriptomic analysis at multiple time points postnoise exposure revealed only subtle changes in expression signatures which appeared to resolve at later time points. However, compared with the controls, mussels exposed to ship noise showed a reduced number of differentially expressed genes in their gill tissue following bacterial challenge. This indicated a suppressed immune response, as indicated by reduced expression of immunerelated genes compared to controls. While bacterial burden and mortality did not significantly differ between noise-exposed and control groups, the proportion of GFP-tagged Vibrio splendidus colonies was higher in noise-exposed mussels.ConclusionsThese findings contribute to a growing body of evidence that anthropogenic noise may impair immune function in bivalves, with implications for aquaculture and marine ecosystem health.